A-172 Evaluating Associations Between the Five Negative Symptom Domains and Cognition in Schizophrenia. (17th August 2022) - Woodyatt, Jessica J; Allen, Daniel N; Goodwin, Grace; Paul, Nina; Salva, Christine; Strauss, Gregory
Abstract: Objective: Recently, factor analysis has supported a five-factor model of negative symptoms in schizophrenia (anhedonia, avolition, alogia, asociality, and blunted affect). Associations between these unique negative symptom domains and neurocognition are yet to be examined. The following study investigates relationships between the five distinct negative symptoms and cognitive functioning. Methods: Outpatients diagnosed with schizophrenia (n=245) were assessed during periods of clinical stability for negative symptom severity using the Brief Negative Symptom Scale (BNSS). The MATRICS Consensus Cognitive Battery (MCCB) was used to assess seven domains of neurocognition, including processing speed, working memory, verbal learning, visual learning, reasoning, problem solving, and social cognition. To evaluate external correlates, the five-domain negative symptoms were correlated with measures of neurocognition. Results: Greater negative associations were found between the five negative symptom domains with processing speed, attention, working memory, social cognition, and overall MCCB scores. Correlational analyses demonstrated the strongest negative relationships between the domain of attention with alogia and blunted affect. Conclusions: The present study examined unique associations between cognitive abilities and the five negative symptom domains. Strong negative associations were found between negative symptoms and distinct measures of neurocognition, indicating a unique variance in cognitive performance correlates with severity of negative symptoms. Results suggest greater severity of negative symptoms is associated with greater impairments in select neurocognitive domains. Further research using analytic approaches would offer additional support for this hypothesis. Findings have implications for developing differential treatments targeting the five negative symptom domains separately, as they may have distinct underlying pathophysiological and neurocognitive mechanisms.